Love Without Food: Supporting Families’ End-of-Life Care Decisions for Critically Ill Late-Stage Cancer Patients - Palmer, Amitabha (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2023)
In some families, there is an inseparable connection between showing love, caring, and providing food. These conceptual connections can create tension between families and care teams over end-of-life care for critically ill late-stage cachexic patients with cancer when families demand that their loved one receive feeds. This case study describes how to dissolve these tensions without compromising the family’s values or the medical team’s ethical duty of nonmaleficence.